THE EFFECT OF ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF ORGANIZATIONAL COMMITMENT - ISKANDAR, GILANG BAGASKARA; ANGGRAENI, ADE IRMA (INDONESIAN RESEARCH SOCIETY, 2018)
Police officers duties and roles in today?s democratic society are getting complex. As theparty whose responsibility is to enforce law and order, it makes their performance matter themost. This research is aimed to figure out the effect of organizational culture on employeeperformance with the mediating role of organizational commitment. The researchmethodology that used in this study is a case study with survey research method. Purposivesampling technique is used to determine the sample for this research. The sample of thisresearch are 200 police officers of Polres Ciamis. SPSS and Amos statistical software arebeing used for data analysis purpose. The results of this study indicate that organizationalculture has a positive effect on both organizational commitment and employee performance.Additionally, organizational commitment has a positive effect on employee performance aswell as mediating the causal relationship between organizational culture and jobperformance. The result of this study is expected to give the implications to Polres Ciamis inincreasing the performance of its officers.